THE ACCELEROMETRIC NETWORK OF THE INDES-MUSA PROJECT IN THE KALOCHORI AREA: CONFIGURATION, DOCUMENTATION AND PRELIMINARY DATA INTERPRETATION - Rovithis, E.; Makra, K.; Savvaidis, A.; Kirtas, E. (Bulletin of the Geological Society of Greece, 2016)
A network of seven accelerometric stations on both ground surface and structures has been recently installed, as part of a multi-sensor network for monitoring seismic motion and ground subsidence in the broader area of Kalochori, west of Thessaloniki in Northern Greece, within the INDES-MUSA project. This network includes ground installations within the urban area, structural stations on top of structures and a freefield station away from the building stock. The documentation of stations is presented including shear wave velocity profiles of the subsoil at each location. A set of thirtynine earthquakes recorded so far by the accelerometric network is reported, followed by data processing procedures performed in the acquired waveforms. Comparisons of the processed earthquake recordings are presented referring to (a) the urban ground and the free-field stations in terms of peak ground acceleration, indicating amplification trends of ground motion, and (b) the structural and the nearby urban ground stations by means of top-to-base ratios in the frequency domain, towards a preliminary identification of the fundamental vibrational characteristics of the instrumented structures. The processed acceleration data are available through the INDES-MUSA Web-GIS portal.